Buckling analysis of layered composite beams with interlayer slip: A force-based finite element formulation. (June 2020) - Santos, H.A.F.A.
Abstract: A force-based finite element formulation for the buckling analysis of two-layer composite beam structures with partial interaction is presented. The geometrically nonlinear beam elements possess a single flexible shear interface and each layer is modelled by means of Timoshenko's theory. The formulation relies on a hybrid variational principle of complementary energy only involving force/moment-like variables as fundamental unknown fields. The approximate field variables are selected such that all equilibrium differential equations are satisfied in strong form. The inter-element equilibrium, as well as Neumann boundary conditions are enforced by means of the Lagrangian-multiplier method. The accuracy and effectiveness of the proposed formulation is demonstrated through the analysis of several numerical tests.